Faktor-Faktor yang Berhubungan dengan Kecelakaan Kerja pada Operator di PT. Pelabuhan Indonesia (PERSERO) Terminal Petikemas Kendari Tahun 2024 - Bagas Rifky Prasetyo; Hartati Bahar; Syawal K. Saptaputra (Pusat Riset dan Inovasi Nasional, 2024)
Occupational Safety and Health (K3) is an aspect of activities in the work environment as a form of implementation of safe and comfortable work to achieve an organizational goal, namely zero incidents so as to increase effectiveness and productivity in the workplace. Workplace accidents can be caused by two things, namely unsafe actions and unsafe conditions. From work accident data, it is estimated that 85% of work accidents occur due to unsafe work behavior and the average accident is caused by human factors. PT. Pelabuhan Indonesia (Persero) Terminal Petikemas Kendari is an Indonesian State-Owned Enterprise engaged in port services, specifically container services. In the past year, there have been 21 accidents involving operators who experienced incidents classified as light at PT. Pelindo. The purpose of this study was to determine the factors related to work accidents among operators at PT. Pelabuhan Indonesia (Persero) Kendari Container Terminal in 2024. The design of this study was cross-sectional using quantitative research methodology. Using a total sampling of 49 peoples. The data analysis technique used the chi-square test and fisher's exact test on the SPSS application. The results showed that there was a relationship between K3 knowledge (0.011), behavior (0.035), use of PPE (0.001) and there was no relationship between supervision (1.000) and work accidents among operators at PT. Pelabuhan Indonesia (Persero) Kendari Container Terminal. The researcher advised the company to improve K3 knowledge, provide rewards as motivation, and carry out punishments to discipline workers.